2018
DOI: 10.1016/j.tourman.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

What pulls ancestral tourists ‘home’? An analysis of ancestral tourist motivations

Abstract: Ancestry has received limited attention within the tourism literature but is shown to play a crucial role in heritage tourism, especially for countries with extended diasporas such as Ireland, Italy India, China, and Scotland. The purpose of this study is to explore ancestral tourist motivations, and attain a broader understanding of this market. A survey of 282 ancestral tourists allowed the identification of three key factors: ancestral tourist motivation; heritage tourist motivations; and mass tourist motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 29 publications
(54 reference statements)
1
46
0
4
Order By: Relevance
“…Recent historical work on tourism has focused on Hilton (Maclean et al, 2017), large multinational hotel development (Quek, 2012), heritage and ancestral tourism (Murdy et al, 2018), and ecotourism development (Jones and Spadafora, 2017). Nevertheless, historical analyses in hospitality and tourism remain relatively few (Heslinga et al, 2018).…”
Section: Historical Work On Tourismmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent historical work on tourism has focused on Hilton (Maclean et al, 2017), large multinational hotel development (Quek, 2012), heritage and ancestral tourism (Murdy et al, 2018), and ecotourism development (Jones and Spadafora, 2017). Nevertheless, historical analyses in hospitality and tourism remain relatively few (Heslinga et al, 2018).…”
Section: Historical Work On Tourismmentioning
confidence: 99%
“…Recent research on tourism in the Scottish Highlands focuses on the role of heritage and history in attracting tourists (Murdy et al, 2018). Consistent with this is recognition of pullfactors (e.g., nature and facilities) in developing tourism and hospitality (Chen and Chen, 2015).…”
Section: Case 1: Aviemore Scottish Highlands (Uk)mentioning
confidence: 99%
“…Travel motivation studies help to better understand and predict factors that influence travel decision‐making (Murdy, Alexander, & Bryce, 2018; Park, Choi, & Lee, 2019; Wong, Cheung, & Wan, 2013). Motivation can be defined as “a state of need, a condition that serves as a driving force to display different kinds of behavior towards certain types of activities, developing preferences, arriving at some expected satisfactory outcome” (Backman, Backman, Uysal, & Sunshine, 1995, p. 15).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies focused on migration (Huang, Hung, and Chen 2018), cultural identity (Li and McKercher 2016; Uriely 1994), well-being (Li and Chan 2017), and cultural connectedness (Weaver, Kwek, and Wang 2017). Yet the study of motivation is crucial to understanding the diaspora tourist typology (Murdy, Alexander, and Bryce 2018; Prayag and Lee 2019). Second, some have suggested that it is particularly difficult to identify the motivations of diaspora tourists, and the current literature on this topic displays a lack of consensus on which motivational factors are meaningful in determining diaspora travel (Huang, Ramshaw, and Norman 2016; Kluin and Lehto 2012; Li and McKercher 2016; Murdy, Alexander, and Bryce 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Yet the study of motivation is crucial to understanding the diaspora tourist typology (Murdy, Alexander, and Bryce 2018; Prayag and Lee 2019). Second, some have suggested that it is particularly difficult to identify the motivations of diaspora tourists, and the current literature on this topic displays a lack of consensus on which motivational factors are meaningful in determining diaspora travel (Huang, Ramshaw, and Norman 2016; Kluin and Lehto 2012; Li and McKercher 2016; Murdy, Alexander, and Bryce 2018). Third, there have been only limited efforts to identity historical linkages between the African homeland and the African diaspora community, consisting of more than 140 million people worldwide (African Development Bank 2018; Gregorius 2016).…”
Section: Introductionmentioning
confidence: 99%